Tingkat Kepadatan Jentik Nyamuk Aedes Aegypti Di Wilayah Kerja Puskesmas Glugur Darat - Yulia Khairina (UPPM Poltekkes Kemenkes Ternate, 2022)
Background :The incidence of DHF in the work area of the UPT Puskesmas Glugur Darat reached 34 cases in 2018 and in 2019 increased to 52 cases. Purpose :Therefore, a research on the density of mosquito larvae was carried out with the aim of knowing the density level of Aedes aegypty mosquito larvae as a vector of dengue fever in the working area of the UPT Puskesmas Glugur Darat.Methods : The type of research used in this research is descriptive research with a cross sectional approach. This research was conducted in the working area of the UPT Puskesmas Glugur Darat. Result :Obtained the value of HI (House Index) 20%, CI (Container Index) 20%, BI (Bruteu Index) 6%, and DF (Density Figure) 4 as medium density. Prevention is to carry out PSN or eradication of mosquito nests.Conclusion :The number of positive larva house in the working area of the UPT Puskesmas Glugur Darat is 6 out of 30 houses, the CI value obtained is 20%. It is known that the number of positive containers larvae is 6 of 30 containers examined, the BI value in the work area of the UPT Puskesmas Glugur Darat is 6%, the value of the Density Figure/ <osquito larva density in the UPT Puskesmas Glugur Darat work area is at a value of 4 which means areas have Medium Density.